Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-03-10T19:02:59+01:00

En estos productos debes aplicar las formulas de

(a + b)²  = a² + 2ab+ b²

(a +b) ³ = a³ + 3a²b+3ab² + b³

(a+b)(a-b) = a² - b²

 

 

 

(17x^(2x+3)h)²  - 2.(17x^(2x+3).h). (21x^(5y-2)) + (21x^(5y-2))²

289 x^(4x+6) .h² - 714. h.x^((2x+3)+(5y-2)) + 441x^(10y - 4)

289x^(4x+6).h² - 714 h x^(2x+5y +1) + 441 x^(10y - 4)

 

 

(13√ h)² - 2 13√h.√27a + (√27a)²

169h - 26√(27ah) + 27a

 

 

(15a^(2x+3)h)³ - 3 (15a^(2x+3)h)² (21ab^(5y-2)) + 3(15a^(2x+3)h) (21ab^(5y-2))² + (21ab^(5y-2))³ =

3375a^(6x+9)h³ - 14175 a^(4x+6)h²ab^(5y-2)) + 19845 a^(2x+3)hab^(10y - 4) + 9261a³b^(15y-6) →resultado final

 

 

 

(5√7p³) ² -  (b^5)² =

25.7.p^6 - b^10 =

175p^6  -   b^10

 

 

espero que te sirva, salu2!!!